TRANSACCIONES INMOBILARIAS REALIZADAS EN COSTA RICA DURANTE EL PERIODO 1800-1850 - Montero, Carlos (2010)
This article is a brief report of the historical data based elaboration processes which contains all Costa Rica’s real state transactions during the first half of 19th century. It explains the elaboration processes step by step, the data base structure of “Transacciones inmobiliarias en Costa Rica durante 1800-1850”, the methodology, its relevance, contributions and limitations.